Influence of Salix babylonica extract addition on in vitro rumen gas production and degradability of ryegrass silage harvested in different cutting days - SALEM, A Z M; KHOLIF, A E; ELGHANDOUR, M M Y; HERNÁNDEZ, J; LIMAS, A G; CIPRIANO, M; CAMACHO, L M; ROJAS, S; OLIVARES, J (The Indian Journal of Animal Sciences, 2016)
Four cutoffs of ryegrass after 15 days (CD15), 30 days (CD30), 45 days (CD45), and 60 days (CD60) with Salix babylonica (SB) extract at 0, 30, and 60 ml/kg ryegrass silage were ensiled for 40 days and then evaluated for the in vitro dry matter (DM) digestibility and gas production (GP). No interactions occurred between cutting day and SB extract for silage’s nutrient contents and in vitro GP. The DM and organic matter (OM) contents were decreased linearly with decreased crude protein (CP), neutral detergent fibres, acid detergent fibres, and acid detergent lignin contents with advancing of days. In contrary, addition of SB extract increased silages’ OM and decreased CP contents. Addition of SB extract for CD15 and CD60 silages, quadratically decreased the lag time. However, SB extract increased the rate of GP and GP during the first 12 h of incubation at the level of 30 ml/kg with CD30 silage and asymptotic GP with the level 60 ml/kg of CD60 silage. Increased DM degradability (DMD) of CD30 and CD60 silages versus decreased DMD with CD15 with increased relative GP (ml gas/g DMD). It could be concluded that CD15 had the highest DM and OM content; however, higher GP was noted with CD45 and CD60. SB extract had weak effects on nutrient content and GP, and the level of 30 ml/kg DM was more effective than the level of 60 ml/kg DM.